Motifs in the tau protein that control binding to microtubules and aggregation determine pathological effects. Issue 1 (December 2017) - Lathuilière, Aurélien; Valdés, Pamela; Papin, Stéphanie; Cacquevel, Matthias; Maclachlan, Catherine; Knott, Graham; Muhs, Andreas; Paganetti, Paolo; Schneider, Bernard
Abstract Tau pathology is associated with cognitive decline in Alzheimer's disease, and missense tau mutations cause frontotemporal dementia. Hyperphosphorylation and misfolding of tau are considered critical steps leading to tauopathies. Here, we determine how motifs controlling conformational changes in the microtubule-binding domain determine tau pathologyin vivo . Human tau was overexpressed in the adult mouse forebrain to compare variants carrying residues that modulate tau propensity to acquire a β-sheet conformation. The P301S mutation linked to frontotemporal dementia causes tau aggregation and rapidly progressing motor deficits. By comparison, wild-type tau becomes heavily hyperphosphorylated, and induces behavioral impairments that do not progress over time. However, the behavioral defects caused by wild-type tau can be suppressed when β-sheet breaking proline residues are introduced in the microtubule-binding domain of tau. This modification facilitates tau interaction with microtubules, as shown by lower levels of phosphorylation, and by the enhanced protective effects of mutated tau against the severing of the cytoskeleton in neurons exposed to vinblastine. Altogether, motifs that are critical for tau conformation determine interaction with microtubules and subsequent pathological modifications, including phosphorylation and aggregation.